Clinical factors associated with a placenta accreta spectrum. (1st September 2021) - Imafuku, Hitomi; Tanimura, Kenji; Shi, Yutoku; Uchida, Akiko; Deguchi, Masashi; Terai, Yoshito
Abstract: Introduction: Placenta accreta spectrum (PAS) is a life-threating obstetric complication, and prenatal prediction of PAS can decrease maternal morbidity and mortality. The aim of this prospective cohort study was to determine the clinical factors associated with PAS. Methods: Pregnant women who delivered at a university hospital were enrolled. Clinical data were collected from medical records, and logistic regression analyses were performed to determine which clinical factors were associated with PAS. Results: Eighty-seven (2.1%) of the 4146 pregnant women experienced PAS. Multivariable analyses revealed that a prior history of cesarean section (CS) (OR 3.3; 95% CI 1.9–5.7; p < 0.01), dilation and curettage (D&C) (OR 2.8; 95% CI 1.7–4.6; p < 0.01), hysteroscopic surgery (OR 5.7; 95% CI 2.3–14.4; p < 0.01), uterine artery embolization (UAE) (OR 44.1; 95% CI 13.8–141.0; p < 0.01), current pregnancy via assisted reproductive technology (ART) (OR 4.1; 95% CI 2.4–7.1; p < 0.01), and the presence of placenta previa in the current pregnancy (OR 13.1; 95% CI 7.9–21.8; p < 0.01) were independently associated with the occurrence of PAS. Conclusion: Pregnant women who have a prior history of CS, D&C, hysteroscopic surgery, UAE, current pregnancy via ART, and the presence of placenta previa in the current pregnancy are high risk for PAS. Highlights: A prior history of uterine artery embolization carries a risk of placenta accreta spectrum. A history of CS, D&C, hysteroscopic surgery is associated with placenta accreta spectrum. ART and placenta previa in the current pregnancy are risk factors for placenta accreta spectrum.